2020
DOI: 10.3390/ijerph17197165
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Pesticide Exposure and Child Respiratory Health

Abstract: Background: Childhood wheeze may be related to pesticide exposure, and diet and genetics (Paroxonase; PON1) may modify the effects of exposure. Methods: We analyzed data from the HOME Study, a prospective pregnancy and birth cohort, to examine the association of gestational urinary organophosphate (OP) and pyrethroid (3PBA) metabolite concentrations with child wheeze, forced expiratory volume in one second (FEV1) at ages 4 and 5 years, and wheeze trajectory patterns through age 8 years. Results: Among 367 sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
4
5
1
Order By: Relevance
“…Similar to our findings, a birth cohort in Cincinnati found null associations of prenatal urinary pyrethroid metabolite concentrations with wheeze among children aged 8, but no current exposure levels were reported. 29 In contrast to our findings, a cohort in New York City reported higher prenatal permethrin and air concentrations were associated with cough, but not wheeze, in children aged 5 years. 30 An analysis among a subset of these children indicated prenatal indoor air PBO (a synergist for pyrethroid insecticides), but not current PBO or permethrin, which was associated with cough at age 5–6 years, but not with asthma or wheeze.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, a birth cohort in Cincinnati found null associations of prenatal urinary pyrethroid metabolite concentrations with wheeze among children aged 8, but no current exposure levels were reported. 29 In contrast to our findings, a cohort in New York City reported higher prenatal permethrin and air concentrations were associated with cough, but not wheeze, in children aged 5 years. 30 An analysis among a subset of these children indicated prenatal indoor air PBO (a synergist for pyrethroid insecticides), but not current PBO or permethrin, which was associated with cough at age 5–6 years, but not with asthma or wheeze.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our findings, a birth cohort in Cincinnati found null associations of prenatal urinary pyrethroid metabolite concentrations with wheeze among children aged 8, but no current exposure levels were reported 29. In contrast to our findings, a cohort in New York City reported higher prenatal permethrin and air concentrations were associated with cough, but not wheeze, in children aged 5 years 30.…”
Section: Discussionsupporting
confidence: 70%
“…Finally, the study by Gilden et al (2020) found an association between gestational exposure to organophosphate pesticides (OPP) and pyrethroid metabolites (3PBA) metabolites with child respiratory symptoms in participants with genetic susceptibility and lower fruit and vegetable consumption (OR: 1.35; 95%CI: 1.013–1.815, p -value: 0.038). This study conducted a secondary data analysis within the Health Outcomes and Measures Of the Environment (HOME) Study, a prospective pregnancy and birth cohort that followed mothers and their children in the greater Cincinnati, Ohio, USA metropolitan area from the second trimester of pregnancy [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, exposure to other components, such as mancozeb and ethylenethiourea, has also shown a positive relationship with children’s respiratory outcomes in the first year of life [ 37 ]. However, some authors [ 30 ] did not find strong associations between gestational pesticide exposure and specific birth defect phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation